1 PENGARUH SUBSTITUSI TEPUNG AMPAS TAHU TERHADAP KUALITAS PILUS - Liana, Rozi Ayu; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was motivated by the price of an expensive cheese, the limited processing of tofu pulp among the public then cheese can be substituted with the utilization of factory waste know namely dried tofu pulp among. So with the utilization of pulp among know at pilus cheese, people was expected to like the tofu pilus know it. The purpose of this research of tofu pulp among much as 10%, 15% and 25% in the processing to see quality of the shapes, color, aroma, texture and taste. This type of research used the methode of random design complete with three repetitions. Analyze data used ANAVA, if Fcount > Ftable then continued with Duncan test. The results showed that there was a significant effect on substitution on the quality of the aroma of tofu pulp, while for the quality of the shape, color, taste, and texture of hedonic test there was no significant difference in effect because Fh <Ft. The results of data analysis of quality of shape (round pointed long end), white color quality, fragrant aroma quality, crisp texture quality, taste quality. Keywords: Tofu Flour Meat, Pilus, Quality